Coherent anti-Stokes Raman scattering for label-free biomedical imaging - Patel, Imran I; Steuwe, Christian; Reichelt, Stefanie; Mahajan, Sumeet (Journal of optics (2010), 2013)
Coherent anti-Stokes Raman scattering (CARS) has established itself as an imaging technique capable of providing video-rate imaging of biological specimens through vibrational coherence of endogenous molecules. Current techniques predominantly involve the application of costly, invasive and potentially non-specific dyes or labels for imaging biomolecules. CARS microscopy can however provide a high-resolution and non-invasive alternative for imaging biomolecules of interest without the need for exogenous labels. Here we provide an overview of CARS including the technique and common instrumentation as well as its applications in biomedical imaging. We discuss the major biomedical areas where CARS has been applied such as in evaluating liver disease, progression of atherosclerosis, tumour classification and tracking drug delivery, whilst also assessing the future challenges for clinical translation.